Caracterización citomorfométrica de Anabaena circinalis (Cyanophyta) presente en una proliferación masiva en el Embalse Paso de las Piedras (Provincia de Buenos Aires, Argentina) - Argañaraz Bonini, Gimena (2005)
Cytomorphometric characterization of Anabaena circinalis (Cyanophyta) from a bloom in the lake Embalse Paso de las Piedras (Buenos Aires Province, Argentina). The principal goal of the work was to make a statistical analysis of the morphology of individuals of Anabaena circinalis growing in a bloom in Embalse Paso de las Piedras (Provincia de Buenos Aires, Argentina), identified by a gene probe for this species. Our results suggest that 1) it is possible to characterise individuals of A. circinalis growing in eutrophic condition, by using statistical parameters of the vegetative cells dimensions, 2) the criterion based on akinete morphology should not be used for characterization given the no maturation of akinetes in eutrophic conditions and the trend to morphological uniformity between the vegetative cells and immature akinetes, and 3) spherical heterocyst and vegetative cells can be discriminated by size but not by shape, whereas both can be differentiated from ovoidal akinetes. The variance analysis of the length of vegetative cells indicates all trichomes belong to the same species.